The effect of exchange rate and consumer price index on macro economic factors of Lao PDR - KEODOUANGKHAM, Phavone; SIPHANTHONG, Bounthavy; SENGDALA, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Through a research of the impact of exchange rates and consumer price indices on the macroeconomic factors of Lao PDR, this study aims to investigate: 1) The fluctuations in exchange rates and changes in consumer price indices within Lao PDR. 2) The effect of exchange rate and consumer price index on macro economic factors of Lao PDR. Utilizing annual data spanning from 1991 to 2022, this study employs the EViews 10 program to conduct analyses using the Error Correction Model (ECM). This methodology facilitates the estimation of both short-term and long-term effects of exchange rates and consumer price indices on macroeconomic variables, specifically Gross Domestic Product (GDP), Trade Value (VT), and Foreign Direct Investment (FDI). The findings are as follows: Observations indicate fluctuations in the exchange rate of the Kip currency against the US dollar over the past 32 years. The exchange rate has exhibited periodic variability, averaging at 7,085.05 Kip per 1 US dollar. On an annual basis, the exchange rate experiences an average change of 439.52 Kip, reflecting a percentage change of 13.70%. Similarly, the consumer price index within Lao PDR demonstrates annual fluctuations. On average, the consumer price index fluctuates by 283.63% each year. Analysis reveals that both exchange rates (EXR) and consumer price indices (CPI) significantly influence Gross Domestic Product (GDP) in the long term, with a confidence level of 95%. However, in the short term, the ability to explain GDP variations lacks statistical significance. The coefficient of the expected value ECM indicates a lack of short-term adjustments for variables to reach long-term equilibrium. Regarding Foreign Direct Investment (FDI), it appears that exchange rates (EXR) do not significantly impact FDI, whereas consumer price indices (CPI) demonstrate a significant effect, with a confidence level of 90% in the long run. However, in the short term, neither exchange rates (EXR) nor consumer price indices (CPI) provide statistically significant explanations for FDI variations.